Good teachers: visions of values and virtues in university student metaphors - Cortazzi, Martin; Jin, Lixian (2020)
Good teachers in university education embody combinations of continuity and change. In the first part here, university teaching is considered in Western philosophies and educational discourse to suggest teacher characteristics and meta-functions, but this article proposes wider internationalised dialogues within humanities which crucially take student views into account. In the second part, we analyse a database of 863 metaphors about teachers given by 439 university students in Malaysia, adopting a socio-cultural approach based on cognitive linguistics. This elicited metaphor analysis explores student views of “good” teachers expressed in such metaphors as “a good teacher is a burning candle” or “a piece of chalk”. Our analysis of metaphor entailments reveals meta-functions and virtues of good teachers which though absent in some official discourses, cohere with the educational philosophy of part one: they include cognitive, social/cultural, affective, moral/spiritual and aesthetic meta-functions. These emphasise the purposes of what teachers “do” and the character of what teachers “are”, as models for what students “do” and what they “become”. This gives challenging insights for teachers (and students) to self-cultivate virtues if these participant visions are taken seriously for learner-centred approaches to humanities in new balances of continuity and change.